Tinjauan Hukum Islam Terhadap Praktik Jual Beli Tanah (Stadi Kasus Di Desa Karangdoro Kecamatan Tegalsari Kabupaten Banyuwangi) - Syafa’at, Abdul Kholiq; Inayah, Nurul; Syafaat, Muhtar (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study aims to determine the practice of buying and selling land in Karangdoro Village, Tegalsari District, Banyuwangi Regency and to find out an overview of Islamic law on the practice of buying and selling land in Karangdoro Village, Tegalsari District, Banyuwangi Regency. The type of research used by the authors in completing this thesis is qualitative descriptive research. The analytical tool used in this study is an interactive model. The results obtained from research regarding the practice of buying and selling land in Karangdoro Village. In buying and selling through a broker, a broker gets 5% of the sales proceeds, where the percentage has become local custom or takes from the addition of the selling price of the land. In addition, usually when a land owner asks for a net price from the sale of land. after knowing the price demanded by the land owner, the broker will find a buyer and offer the goods. After the broker has agreed on a price with the buyer, the buyer will meet with the land owner to enter into an agreement or agreement. The sale and purchase transaction of land in Karangdoro Village is valid according to Islamic law, because it complies with the terms and conditions of sale and purchase, and the addition of prices by brokers in selling land is permissible under Islamic law because they have obtained permission from the land owner. So from the results of the research that the researchers did, it can be concluded that the provisions of Islamic law regarding the practice of buying and selling land in Karangdoro Village, Tegalsari District, Banyuwangi Regency, the practice of buying and selling that is carried out is valid because it complies with the terms and pillars of buying and selling and adding prices by the broker is legally permissible Islam.